Between zero-deforestation and zero-tolerance from the state: Navigating strategies of palm oil companies of Indonesia - Dermawan, A.; Hospes, O.; Termeer, C.J.A.M. (Elsevier, 2022)
Since late 2013, Indonesia's biggest palm oil companies have positioned themselves as strong advocates of zero-deforestation. However, their commitments to zero-deforestation have not always been well-received by the Indonesian government. The government has taken many initiatives to promote sustainable palm oil and to put an end to deforestation, but prefers to do so on its own terms. The palm oil companies have had to organize and frame their zero-deforestation policies vis-a-vis the government strategically. Our research question is: how have the major palm oil companies of Indonesia navigated their zero-deforestation commitment around Indonesian public authorities' regulatory power? Using the concept of corporate political activity, we distinguish three episodes of corporate zero-deforestation commitment, each characterized by different strategies of companies. We show that palm oil companies have changed the strategies of implementing their zero-deforestation policies from trying to influence government policy to operating in the shadow of hierarchy.